Implementation of the Independent Learning Curriculum in the Subject of Pancasila and Civic Education - Theodorus Pangalila,; Diana Darmayanti Putong,; Mario R. Lengkong,; Fitriyani Mamonto, (Technium Education and Humanities, 2024)
This study aims to determine the effect of applying the Independent Learning Curriculum in Pancasila and Civic Education subjects in the experimental class with the average learning outcomes of lessons in the control class using the 2013 curriculum. The method used in this research is the Experimental method with the research design used is that the experimental group is given treatment, namely using the independent learning curriculum (x) and the control group in its learning uses the 2013 curriculum (y). The sample in this study were all students of class VII A and class VII B of the Catholic Junior High School of the Sacred Heart of Manado totaling 38 students, consisting of two classes, namely the control class totaling 18 students and the experimental class totaling 20 students. The variables and indicators used are independent variables and dependent variables. In data collection techniques using observation and research instruments. Based on the results of the study, it shows that there is a significant influence on learning outcomes in Pancasila and Civic Education subjects in class VII students of the Catholic Junior High School of the Sacred Heart of Manado.